Representasi Budaya Islam Kontemporer dalam Kajian Dhuha: Perspektif Semiotika - Muhtadiah Hasibuan; Sulaiman RM; Fakhrur Rozi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to analyze the representation of contemporary Islamic culture in the Dhuha program aired on the AW Sumut Channel YouTube, using Roland Barthes' semiotic analysis, which allows the researcher to interpret the symbols and signs used in the program. The findings reveal that Dhuha presents Islamic culture by combining traditional and contemporary symbols, such as the use of colors, clothing, and words in the sermons that are relevant to current social dynamics. Further discussion uncovers that the program not only conveys religious messages but also plays a role in shaping Islamic cultural identity in the digital era, by adjusting visual and narrative elements to attract an audience from diverse backgrounds. In conclusion, the representation of Islamic culture in Dhuha Online reflects the adaptation and modernization of Islamic preaching, which continues to uphold religious values while being tailored to the development of technology and the needs of modern society.